Emerging citizenship regimes and rescaling (European) nation-states: algorithmic, liquid, metropolitan and stateless citizenship ideal types - Calzada, I (Edward Elgar Publishing, 2020)
This chapter examines how state spaces throughout Europe are facing structural tensions as traditional ethnic nationalism increasingly comes into conflict with urban transformations. It argues that European citizenship is experiencing a unique set of city-regional and techno-political dynamics consisting of: (1) geotechnologics (driven by blockchain), (2) geopolitics (driven by dataism, the ideology of big data’s determinism), (3) geoeconomics (driven by populism), and (4) geodemocratics (driven by devolution). Given these tensions and their associated claimed rights, how will nation-states evolve? Will the urban age reconfigure the politics of nation-states through new and emerging citizenship regimes? Specifically, will the European Union evolve towards a post-national polity from a platform of established nation-states? Or will it head for a city-regionalized federal network of nations determined voluntarily and democratically? The chapter develops the concept of emerging citizenship regimes as a new theoretical framework for thinking about state rescaling by proposing four ideal types of citizenship: algorithmic, liquid, metropolitan and stateless. It challenges the existing interpretation of how current citizenship regimes are transforming the city-regional and techno-political configuration of European nation-states.